Decolonizing Global Health Education: Rethinking Institutional Partnerships and Approaches. (28th April 2020) - Eichbaum, Quentin G.; Adams, Lisa V.; Evert, Jessica; Ho, Ming-Jung; Semali, Innocent A.; van Schalkwyk, Susan C.
Abstract : Global health often entails partnerships between institutions in low- and middle-income countries (LMICs) that were previously colonized and high-income countries (HICs) that were colonizers. Little attention has been paid to the legacy of former colonial relationships and the influence they have on global health initiatives. There have been recent calls for the decolonization of global health education and the reexamination of assumptions and practices under pinning global health partnerships. Medicine's role in colonialism cannot be ignored and requires critical review. There is a growing awareness of how knowledge generated in HICs defines practices and informs thinking to the detriment of knowledge systems in LMICs. Additionally, research partnerships often benefit the better-resourced partner. In this article, the authors offer a brief analysis of the intersections between colonialism, medicine, and global health education and explore the lingering impact of colonialist legacies on current global health programs and partnerships. They describe how "decolonized" perspectives have not gained sufficient traction and how inequitable power dynamics and neocolonialist assumptions continue to dominate. They discuss 5 approaches, and highlight resources, that challenge colonial paradigms in the global health arena. Furthermore, they argue for the inclusion of more transfor mative learning approaches to promote change in attitudes and practice. They call for critical reflection and concomitant action to shift colonial paradigms toward more equitable partnerships in global education.